Environmental Impact Assessment of a School Building in Iceland Using LCA-Including the Effect of Long Distance Transport of Materials - Nargessadat Emami; Björn Marteinsson; Jukka Heinonen (Buildings, 2016)
Buildings are the key components of urban areas and society as a complex system. A life cycle assessment was applied to estimate the environmental impacts of the resources applied in the building envelope, floor slabs, and interior walls of the Vættaskóli-Engi building in Reykjavik, Iceland. The scope of this study included four modules of extraction and transportation of raw material to the manufacturing site, production of the construction materials, and transport to the building site, as described in the standard EN 15804. The total environmental effects of the school building in terms of global warming potential, ozone depletion potential, human toxicity, acidification, and eutrophication were calculated. The total global warming potential impact was equal to 255 kg of CO2 eq/sqm, which was low compared to previous studies and was due to the limited system boundary of the current study. The effect of long-distance overseas transport of materials was noticeable in terms of acidification (25%) and eutrophication (31%) while it was negligible in other impact groups. The results also concluded that producing the cement in Iceland caused less environmental impact in all five impact categories compared to the case in which the cement was imported from Germany. The major contribution of this work is that the environmental impacts of different plans for domestic production or import of construction materials to Iceland can be precisely assessed in order to identify effective measures to move towards a sustainable built environment in Iceland, and also to provide consistent insights for stakeholders.